2021
DOI: 10.1007/978-3-030-71995-1_27
|View full text |Cite
|
Sign up to set email alerts
|

The Structure of Sum-Over-Paths, its Consequences, and Completeness for Clifford

Abstract: We show that the formalism of “Sum-Over-Path” (SOP), used for symbolically representing linear maps or quantum operators, together with a proper rewrite system, has the structure of a dagger-compact PROP. Several consequences arise from this observation:– Morphisms of SOP are very close to the diagrams of the graphical calculus called ZH-Calculus, so we give a system of interpretation between the two– A construction, called the discard construction, can be applied to enrich the formalism so that, in particular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(39 citation statements)
references
References 13 publications
3
17
0
Order By: Relevance
“…We begin by briefly reviewing the theory of path sums [2,31]. A path sum representation of a linear operator Ψ : C 2 m → C 2 n is an expression for Ψ as a sum indexed by binary variables such as…”
Section: Path Sumsmentioning
confidence: 99%
See 4 more Smart Citations
“…We begin by briefly reviewing the theory of path sums [2,31]. A path sum representation of a linear operator Ψ : C 2 m → C 2 n is an expression for Ψ as a sum indexed by binary variables such as…”
Section: Path Sumsmentioning
confidence: 99%
“…The sum-over-paths representations of linear operators has been studied extensively in the context of quantum information [13,9,27,24,19,14]. Recent work on the connection to graphical calculi [20,31] has shown that path sums form a universal model for linear operators over 2 n -dimensional Hilbert spaces through direct translations from universal graphical calculi such as the ZH-calculus [7].…”
Section: Path Sumsmentioning
confidence: 99%
See 3 more Smart Citations